Switching Behavior of Banks' Customers: Does It Exist? - Utami, Rizky; Arif, Hermita; Habbe, Abdul Hamid; Abdullah, Faisal (Faculty of Economics and Business, Hasanuddin University, 2024)
Ideally, Indonesia with the largest Muslim population in the world is able to optimize its potential to become the prominent global player in Islamic finance industry. Unexpectedly, Indonesia is ranked at 9th position of global Islamic banking market. Despite the strong support from both government and society, it is ironic thatÂ the market share of Islamic bank in Indonesia has just reached 7.09% in 2022, far below its conventional counterpart, in its three decades of age. Employing descriptive quantitative approach, this study examines the presence of switching behavior of society in Indonesia by addressing why the impact of switching behavior has small impact on the market share improvement in the context of Indonesia. A total of 128 respondents were filling the questionnaire based on purposive random sampling fulfilling the criteria of being customer of both Islamic and conventional bank as well as currently working.Â